Interlanguage Pragmatics: Iranian EFL Teachers’ Cognition (Alberta Journal of Educational Research, 2019)
In curricula where teachers have agency to make decisions on everyday classroom activities, their cognition exerts strong influences on their pedagogical practices. The present paper reports on a qualitative multiple-case study exploring Iranian English as a Foreign Language (EFL) teachers’ cognition of interlanguage pragmatics. Through triangulation of multiple methods and data sources, the study details descriptions of five Iranian EFL teachers’ classroom practices, the cognitions behind these practices, and the way their cognition and the teaching context interact in shaping their everyday teaching practices. The findings suggest that underrepresentation of pragmatic competence in the EFL classes can be attributed to contextual factors such as deficiency in the EFL teachers’ content and pedagogic content knowledge of interlanguage pragmatics and curricular decisions. The main findings are then discussed against the backdrop of the literature on interlanguage pragmatics.Keywords: Interlanguage pragmatics, language teacher cognition, belief, EFL teacher, EFL teacher knowledge baseDans les programmes où les enseignants ont le pouvoir décisionnel quant aux activités quotidiennes en salle de classe, les connaissances des enseignants exercent une grande influence sur leurs pratiques pédagogiques. Cet article fait état d’une étude qualitative multi-cas portant sur les connaissances en pragmatique interlangue qu’ont des enseignants iraniens d’anglais langue étrangère (ALE). Par une triangulation de nombreuses méthodes et sources de données, l’article décrit en détail les pratiques en salle de classe de cinq enseignants iraniens d’ALE, les connaissances qui sous-tendent ces pratiques et la façon dont leurs connaissances et le contexte d’enseignement interagissent pour façonner les pratiques pédagogiques quotidiennes. Les résultats indiquent que la sous-représentation d’une compétence pragmatique dans les cours d’ALE serait attribuable à des facteurs contextuels tels des lacunes dans les connaissances, chez les enseignants d’ALE, relatives au contenu et à la pédagogie en matière de pragmatique interlangue et aux décisions concernant le programme. Nous discutons des résultats principaux dans le contexte de la documentation sur la pragmatique interlangue. Mots clés : pragmatique interlangue; connaissances des enseignants de langue; croyance; enseignant d’ALE; connaissances fondamentales des enseignants d’ALE